Editor's Choice – Asymptomatic Carotid Stenosis and Cognitive Impairment: A Systematic Review. (June 2021) - Paraskevas, Kosmas I.; Faggioli, Gianluca; Ancetti, Stefano; Naylor, A.Ross
Abstract : Objective: The aim was to evaluate the relationship between asymptomatic carotid stenosis (ACS) of any severity and cognitive impairment and to determine whether there is evidence supporting an aetiological role for ACS in the pathophysiology of cognitive impairment. Data sources: PubMed/Medline, Embase, Scopus, and the Cochrane library. Review methods: This was a systematic review (35 cross sectional or longitudinal studies) Results: Study heterogeneity confounded data interpretation, largely because of no standardisation regarding cognitive testing. In the 30 cross sectional and six longitudinal studies (one included both), 33/35 (94%) reported an association between any degree of ACS and one or more tests of impaired cognitive function (20 reported one to three tests with poorer cognition; 11 reported four to six tests with poorer cognition, while three studies reported seven or more tests with poorer cognition). There was no evidence that ACS caused cognitive impairment via silent cortical infarction, or via involvement in the pathophysiology of lacunar infarction or white matter hyperintensities. However, nine of 10 studies evaluating cerebral vascular reserve (CVR) reported that ACS patients with impaired CVR were significantly more likely to have cognitive impairment and that impaired CVR was associated with worsening cognition over time. Patients with severe ACS but normal CVR had cognitive scores similar to controls. Conclusion: Notwithstanding significant heterogeneity within the constituent studies, which compromised overall interpretation, 94% of studies reported an association between ACS and one or more tests of cognitive impairment. However, "significant association" does not automatically imply an aetiological relationship. At present, there is no clear evidence that ACS causes cognitive impairment via silent cortical infarction (but very few studies have addressed this question) and no evidence of ACS involvement in the pathophysiology of white matter hyperintensities or lacunar infarction. There is, however, better evidence that patients with severe ACS and impaired CVR are more likely to have cognitive impairment and to suffer further cognitive decline with time.